Implementation of Learning Through Direct Instruction Plus Based on Interavcive Media Flipbook in Curtural Arts and Crafts Lessons at MIN 1 Medan - Rika Restela; Juwita Tindaon; Sriadhi Sriadhi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
The teaching and learning process is inseparable from the application of learning models and media. The Direct Instruction Plus model based on Flipbook Interactive Media is used as a tool and way to achieve lesson objectives. This study aims to determine the learning outcomes of MIN 1 Medan students after using Direct Instruction Plus based on Flipbook Interactive Media. This research uses a type of classroom action research with a qualitative descriptive approach. Data collection techniques used in this study are observation sheets, work results and documentation. Data analysis in this study uses the calculation of the percentage of analysis of teacher observation results, students and learning outcomes. The results of this study were obtained, in cycle I teacher activity obtained a percentage score of 72% with the categorization of